Radiotherapy Response Assessment of Multiple Myeloma: A Dual-Energy CT Approach With Virtual Non-Calcium Images - Fervers, Philipp; Celik, Erkan; Bratke, Grischa; Maintz, David; Baues, Christian; Ruffing, Simon; Pollman-Schweckhorst, Philip; Kottlors, Jonathan; Lennartz, Simon; Große Hokamp, Nils (Frontiers in Oncology, 2021)
Background: Life expectancy of patients with multiple myeloma (MM) has increased over the past decades, underlining the importance of local tumor control and avoidance of dose dependent side effects of palliative radiotherapy (RT). Virtual non-calcium (VNCa) imaging from dual-energy computed tomography (DECT) has been suggested to estimate cellularity and metabolic activity of lytic bone lesions (LBL) in MM. Objective: To explore the feasibility of RT response monitoring with DECT-derived VNCa attenuation measurements in MM. Methods: Thirty-three patients with 85 LBLs that had been irradiated and 85 paired non-irradiated LBLs from the same patients were included in this retrospective study. Irradiated and non-irradiated LBLs were measured by circular regions of interest (ROI) on conventional and VNCa images in a total of 216 follow-up measurements (48 before and 168 after RT). Follow-ups were rated as therapy response, stable disease or local progression according to the MD Anderson criteria. Receiver operating characteristic (ROC) analysis was performed to discriminate irradiated vs. non-irradiated and locally progressive vs. stable/responsive LBLs, using absolute attenuation post-irradiation and percentage attenuation change for patients with pre-irradiation DECT, if available. Results: Attenuation of LBLs decreased after RT depending on the time that had passed after irradiation (absolute thresholds for identification of irradiated LBLs 30.5 – 70.0 HU (best area under the curve (AUC) 0.75 [0.59 – 0.91]) and -77.0 – -22.5 HU (best AUC 0.85 [0.65 – 1.00]) / -50% and -117% – -167% proportional change of attenuation on conventional and VNCa images, respectively). VNCa CT was significantly superior for identification of RT effects in LBLs with higher calcium content (best VNCa AUC 0.96 [0.91 – 1.00], best conventional CT AUC 0.64 [0.45 – 0.83]). Thresholds for early identification of local irradiation failure were >20.5 HU on conventional CT (AUC 0.78 [0.68 – 0.88]) and >-27 HU on VNCa CT (AUC 0.83 [0.70 – 0.96]). Conclusion: Therapy response of LBLs after RT can be monitored by VNCa imaging based on regular myeloma scans, which yields potential for optimizing the lesion-specific radiation dose for local tumor control. Decreasing attenuation indicates RT response, while above threshold attenuation of LBLs precedes local irradiation failure.